Cabassous chacoensis (Cingulata: Dasypodidae). (11th September 2014) - Hayssen, Virginia
Abstract: Cabassous chacoensis (Chacoan naked-tailed armadillo) is a little-studied, primarily fossorial armadillo endemic to xeric parts of the Gran Chaco in western Paraguay and northern Argentina. C. chacoensis is listed as "Near Threatened" by the International Union for Conservation of Nature and Natural Resources.